Intervention “Taman Pemulihan Gisi” to Provide Wasting Children with Additional Food to Prevent Stunting - Probowati, Ririn; Ratnawati, Mamik; Savitri, Monika; Wibowo, Heri; Wahyu, Fransiska (Indonesian Journal of Global Health Research, 2024)
Stunting is a trending health problem in society, to overcome this there is one government policy, namely the Taman Pemulihan Gisi (TPG) activity which is useful for improving the nutritional status of toddlers. Research objectives: To determine the effect of supplementary feeding through TPG on the nutritional status of wasting children Pre-experimental research design (one-group pre-posttestdesign), Population: all 20 toddlers experiencing wasting in 2023 with total sampling technique. Independent Variable: Supplemental feeding. Dependent variable: change in body weight with an instrument measuring body weight using scales before and after giving additional food for 14 days, and health status (sick/ever been sick) using a questionnaire during the intervention. Data analysis using uji sperman rank. Research results Most (62.5%) aged 3-4 years with increased weight. with ρ=0.000 there is an effect of food provision on changes in body weight based on age group. The majority (77.8%) were men who experienced weight gain. with ρ=0.001 there is an effect of feeding on body weight based on gender. The majority (72.7%) changed weight and experienced illness when given additional food at TPG ρ=0.027, there was an influence of additional feeding on changes in weight based on whether the child had been sick. Providing additional food to children that meets the quality and quantity of food will have a direct impact on changes in body weight. In TPG activities carried out with cadres, health workers and mothers of toddlers for 14 days, there is health education to prepare menus of various types, cooking methods, determining the content and appearance of food so that children increase their appetite for the maintenance and repair of body cells and life processes. Children and mothers, cadres and health workers gather in TPG activities every day to carry out weight checks, health status checks and education for mothers on how to prepare menus for children. There was an increase in weight in children who received additional food in TPG activities. There was an increase in weight in children who received additional food in TPG activities. Good cooperation between mothers, cadres and health workers during the implementation of supplementary feeding through TPG is the key to success in increasing changes in the nutritional status of wasting children.